Sejarah Perkembangan Pelabuhan Belawan, 1950-1990 - Batubara, Septina P; Gultom, Elisabeth S.; Sianturi, Donacia F. (Innovative: Journal Of Social Science Research, 2024)
This research aims to find out how the port developed from 1950 to 1990. This development can be seen by explaining the development of the Belawan area itself, such as the topography of the area which makes it easier to access and the fertility of the land, the progress of the port as seen from exports and imports. as well as the flow of ships going back and forth. This research uses one method and two approaches, namely the city history method and data collection using a qualitative and quantitative approach. Based on the research results, it was found that the exports and imports of the Belawan port greatly influenced the port itself. The physical development of the port includes mud dredging, docks, warehouses, construction of office buildings, roads and railways. Port facilities have been expanded to provide electricity and clean water. In the administrative sector, Belawan Port is currently a port company under the auspices of PELINDO. The construction of Belawan Port has increased imports and exports of Belawan Port. The construction of Belawan Port will affect the lives of the people of Deli, including urban morphology, social infrastructure, employment and commercial changes.